The reproductive behavior of Neotropical dung beetles - Huerta, Carmen; Cruz-Rosales, Magdalena; González-Vainer, Patricia; Chamorro-Florescano, Ivette; Rivera, José D.; Favila, Mario E. (Frontiers in Ecology and Evolution, 2023)
Dung beetles display complex reproductive behaviors involving sexual findings, sexual recognition, fighting for mates and food used for nesting, sperm competition, and parental care. Over the past 40 years, significant advances have been made regarding the knowledge of various aspects of the sexual and nesting behavior of Neotropical dung beetles. However, human activities modify the natural habitats of dung beetles at an alarming rate, affecting food availability and altering the ecological functions performed by the species in their different habitats. A deeper understanding of the reproductive behavior of dung beetles may contribute significantly in understanding the evolutionary diversification of these insects and their response to environmental changes. The present study reviews and analyzes studies regarding the sexual and reproductive behavior of Neotropical dung beetle species under field and laboratory conditions. We gathered 132 studies and 146 species; 42% of the available data were based on field observations, 23% on laboratory observations, 30% under both field and laboratory conditions, and 5% unspecified. Our review detected significant knowledge, geographic, and habitat gaps regarding the reproductive behavior of Neotropical dung beetles. Based on our findings, we propose future research goals and alternative methods to measure the behavioral responses of Neotropical dung beetles to the impacts of human activities.